00.04: Structural fire design – Developments in research and assessment of fire in steel and composite structures. (13th September 2017) - Knobloch, Markus
ABSTRACT: This paper addresses structural fire safety, which is a key consideration in the design of buildings, and a topic attracting worldwide attention. Significant advances in research have increased our knowledge on the behaviour of steel and steel‐concrete composite structures in fire. Some areas are becoming well understood (like the behaviour of isolated elements in conventional building materials), while others areas (such as global behaviour of structures in fire, or constitutive modelling of innovative building materials at elevated temperatures) need further investigation. It is the aim of this paper to review progress in this area and to present latest developments with respect to future European structural fire design.